Death gods: an encyclopedia of the rulers, evil spirits, and geographies of the dead - Abel, Ernest L. (Greenwood Press, 2009)
This book examines the culture and beliefs regarding life after death. In cultures throughout human history, people have believed that some part of themselves continued to exist after they died. Part of that belief is that living can influence what happens to the dead in the afterlife, and that the dead can return from the afterlife to affect the living. "Death Gods" describes the many ways the afterlife - especially that part of the afterlife commonly known as 'Hell' - has been characterized in myths from around the world. The hundreds of entries provide readers with a guide to the afterlife as portrayed in these myths - its geography, its rulers, its inhabitants, how they got there, and what happens after their arrival. While the Devil is a prominent resident and ruler of the afterworld in many religions, especially Christianity, this book examines many other versions of Hell whether presided over by the Devil, Hades, or one of the many other rulers of the dead.This book provides concise encyclopedic entries on all aspects of the mythology of the afterlife including:the underworlds form the myths of cultures from across the globe - for example, Xibalba, the underworld of the Quiche Maya; Di Yu, the underground realm of the dead in Chinese mythology; the gods and demons of the afterlife - the Hindu god of death and justice Yama; Ahriman, the evil twin of the benevolent god Ahura; Mazda in Zoroastrian mythology; and, Buso, the invisible ghouls who haunt graveyards and feed on human corpses in Philippine mythology. The volume also includes an extensive bibliography of the most useful resources for understanding the mythology of death and the afterlife.